2012
DOI: 10.1128/aem.00577-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Complementation of the Obligate Marine Actinobacterium Salinispora tropica with the Large Mechanosensitive Channel Gene mscL Rescues Cells from Osmotic Downshock

Abstract: ABSTRACTMarine actinomycetes in the genusSalinisporafail to grow when seawater is replaced with deionized (DI) water in complex growth media. While bioinformatic analyses have led to the identification of a number of candidate marine adaptation genes, there is currently no experimental evidence to support the genetic basis for the osmotic requirements associated with this taxon. One hypothesis is that the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Marine adaptation genes (MAGs) were identified from S. tropica and S. arenicola by comparative genomic analysis, and the loss of a mechanosensitive channel gene mscL was thought to result in the inability of Salinispora strains to grow in low osmotic environment. The finding was later confirmed by genetic complementation of S. tropica with mscL ( Bucarey et al, 2012 ). By the genomic comparison of two sponge-derived Streptomyces albus isolates with their terrestrial relative S. albus J1074, several putative MAGs linked to electron transport and potassium uptake were identified ( Ian et al, 2014 ).…”
Section: Introductionmentioning
confidence: 78%
“…Marine adaptation genes (MAGs) were identified from S. tropica and S. arenicola by comparative genomic analysis, and the loss of a mechanosensitive channel gene mscL was thought to result in the inability of Salinispora strains to grow in low osmotic environment. The finding was later confirmed by genetic complementation of S. tropica with mscL ( Bucarey et al, 2012 ). By the genomic comparison of two sponge-derived Streptomyces albus isolates with their terrestrial relative S. albus J1074, several putative MAGs linked to electron transport and potassium uptake were identified ( Ian et al, 2014 ).…”
Section: Introductionmentioning
confidence: 78%
“…The majority of their secondary metabolite biosynthetic gene clusters are located in genomic islands, which was used to suggest the products provide ecologically relevant adaptive traits 36 . The genus is unique among the Micromonosporaceae in that all strains tested to date fail to grow when seawater is replaced with deionized water in the growth medium, which was subsequently linked to a variety of marine adaptation genes using both bioinformatic 37 and experimental approaches 38 . However, the primary interest in this taxon has focused on its ability to produce unique and biologically active secondary metabolites.…”
Section: Discovery Of the Genusmentioning
confidence: 99%
“…Loss of a particular gene encoding a mechanosensitive channel required for growth in the media with low osmotic strength has been noted for Salinispora . Later, Bucarey et al [5] have demonstrated that complementation of this lost gene restores the capacity of Salinispora to grow on media without sea water. Unfortunately, only a few genome sequences of marine actinomycetes are currently available, thus making studies on marine adaptation of these bacteria rather difficult.…”
Section: Introductionmentioning
confidence: 99%